2018
DOI: 10.1038/s41590-018-0049-7
|View full text |Cite|
|
Sign up to set email alerts
|

Natural variation in the parameters of innate immune cells is preferentially driven by genetic factors

Abstract: The quantification and characterization of circulating immune cells provide key indicators of human health and disease. To identify the relative effects of environmental and genetic factors on variation in the parameters of innate and adaptive immune cells in homeostatic conditions, we combined standardized flow cytometry of blood leukocytes and genome-wide DNA genotyping of 1,000 healthy, unrelated people of Western European ancestry. We found that smoking, together with age, sex and latent infection with cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

32
275
4
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 238 publications
(316 citation statements)
references
References 73 publications
32
275
4
5
Order By: Relevance
“…From analysis of the Milieu Interieur cohort we recently identified both genetic and non-genetic determinants that contribute to variance within circulating immune cell populations. 7 As immune cells are the major targets for most vaccines it is important to understand how and why they may differ between individuals. Leveraging the 1,000 well-defined healthy donors and the associated metadata, we identified a significant impact of age, sex and latent cytomegalovirus (CMV) infection on numbers of adaptive immune cells such as T and B cells.…”
Section: Dissecting Immune Response Variabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…From analysis of the Milieu Interieur cohort we recently identified both genetic and non-genetic determinants that contribute to variance within circulating immune cell populations. 7 As immune cells are the major targets for most vaccines it is important to understand how and why they may differ between individuals. Leveraging the 1,000 well-defined healthy donors and the associated metadata, we identified a significant impact of age, sex and latent cytomegalovirus (CMV) infection on numbers of adaptive immune cells such as T and B cells.…”
Section: Dissecting Immune Response Variabilitymentioning
confidence: 99%
“…Leveraging the 1,000 well-defined healthy donors and the associated metadata, we identified a significant impact of age, sex and latent cytomegalovirus (CMV) infection on numbers of adaptive immune cells such as T and B cells. 7 These are the immune cells whose differentiation into long-lived memory cells is the classical hallmark of successful vaccination. Taking advantage of our age-balanced cohort we showed that naïve CD8 + T cells decrease more than twice as rapidly with age as compared to naïve CD4 + T cells (3.5% and 1.5% per year, respectively) showing how age may significantly impact vaccines that target these cellular populations.…”
Section: Dissecting Immune Response Variabilitymentioning
confidence: 99%
See 3 more Smart Citations